Structure and free volume of fluorine-containing polyetherimides with pendant di-tert-butyl groups investigated by molecular dynamics simulation. (14th October 2022) - Mazo, Mikhail; Khudobin, Roman; Balabaev, Nikolay; Belov, Nikolay; Ryzhikh, Victoria; Nikiforov, Roman; Chatterjee, Rimpa; Banerjee, Susanta
Abstract: The study is focused on the investigation of structural properties of 5 polyetherimides (PEIs) containing 1, 4-bis-[2′-trifluoromethyl 4′-(4″-aminophenyl)phenoxy]-2, 5-di-tert-butylbenzene diamine monomer (FMTBDA) and 5 different dianhydride monomers (PMDA, BTDA, ODPA, 6FDA, and BPADA) using molecular dynamics simulations. 32 independent models were built for each polymer. Densities calculated for the modeled samples were compared with the experimental ones, giving difference of up to 6%. Accessible free volume (AFV) distribution was evaluated for the investigated polymers. It was shown that AFV for all the probe sizes decreased in a row: PMDA > BTDA∼6FDA > ODPA > BPADA, which is in line with the experimental gas transport parameters shown previously. Bimodal AFV distribution was demonstrated. Specific surface area (SSA) was calculated for the models of polymers, and fragments composing the inner surface of the free volume were determined. Analysis of the elements of the free volume surface has shown that sp 3 carbon (Сsp3 ), carbonyl oxygen (OC=O ), and fluorine (F) atoms tend to form free volume elements, while imide nitrogen (Nimide ) and ether oxygen (Oether ) tend to compose polymer bulk. Graphical abstract: Image 1 Highlights: Accessible cavities distribution shows bimodal behavior for FMTBDA PEIs. CSp3, carbonyl oxygen and fluorine atoms tend to form free volume elements. Imide nitrogen and ether oxygen tend to compose FMTBDA PEIs polymer bulk. ∼50% of H2 AFV in FMTBDA PEIs is also accessible to molecules larger than O2 .